Business Process Improvement for Reducing Delay in the Material Document Issue Process in the Fertiliser Manufacturing Industry - Anastasia Lidya Maukar; Jhindan Iqbal Fiasta (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2023)
The business process will be carried out by the fertiliser company. Currently, process delays are a problem for one of the departments in this company. The delay contributor is an unsatisfied 3.5% gap rate in the material document issue process key performance indicator (KPI). This will disrupt the process flow and can have a domino effect on end-users. Business process improvement (BPI) is one of the most powerful and effective methods to use for improving the business process and business process modeling notation (BPMN) provides a notation that is simple to understand for analysis of the business process. The result of the BPI tool is the design of a new business system with improved processes modeled using Bizagi Modeler, because several processes are still handled manually. So, the processing time is long and needs to be evaluated. Some of the activities will be elimination, upgrading, and simplification. The percentage increase in the total time of the proposed business process is 7% in the KPI. The process time decrease in the total time of the proposed business process is 10.90 days. Further research should be conducted to reduce delays in the material document issue process for the next levels, such as resource analysis and calendar analysis, it will be able to figure out what method is more appropriate for business process improvement in the material document issue.